Вы находитесь на странице: 1из 6

“JUST THE MATHS”

UNIT NUMBER

12.4

INTEGRATION 4
(Integration by substitution in general)

by

A.J.Hobson

12.4.1 Examples using the standard formula


12.4.2 Integrals involving a function and its derivative
12.4.3 Exercises
12.4.4 Answers to exercises
UNIT 12.4 - INTEGRATION 4
INTEGRATION BY SUBSTITUTION IN GENERAL

12.4.1 EXAMPLES USING THE STANDARD FORMULA

With any integral Z


f (x)dx,
it may be convenient to make some kind of substitution relating the variable, x, to a new
variable, u. In such cases, we may use the formula discussed in Unit 12.1, namely
Z Z
dx
f (x)dx = f (x) du,
du
where it is assumed that, on the right hand side, the integrand has been expressed wholly
in terms of u.

For this Unit, substitutions other than linear ones will be given in the problems to be solved.

EXAMPLES

1. Use the substitution x = a sin u to show that


Z
dx x
√ = sin−1 + C.
a2−x 2 a

Solution
To be precise, we shall assume for simplicity that u is the acute angle for which x =
a sin u. In effect, we shall be making the substitution u = sin−1 xa using the principal

value of the inverse function; we can certainly do this because the expression a2 − x2
requires that −a < x < a.
dx
If x = a sin u, then du = a cos u, so that the integral becomes
Z
a cos u
√ du.
a2 − a2 sin2 u
But, from trigonometric identities,
q
a2 − a2 sin2 u ≡ a cos u,
both sides being positive when u is an acute angle.
We are thus left with Z
x
1du = u + C = sin−1 + C.
a

1
1
2. Use the substitution u = x
to determine the indefinite integral
Z
dx
z= √ .
x 1 + x2
Solution
Converting the substitution to the form
1
x= ,
u
we have
dx 1
= − 2.
du u
Hence, Z
1 1
z= q .− du
1
1+ 1 u2
u u2
That is, Z
1 √
z= −√ = − ln(u + u2 + 1) + C.
u2 + 1
Returning to the original variable, x, we have
 s 
1 1
z = − ln  + + 1 + C.
x x2

Note:
This example is somewhat harder than would be expected under examination condi-
tions.

12.4.2 INTEGRALS INVOLVING A FUNCTION AND ITS DERIVATIVE

The method of integration by substitution provides two useful results applicable to a wide
range of problems. They are as follows:

(a)
Z
[f (x)]n+1
[f (x)]n f 0 (x)dx = +C
n+1
provided n 6= −1.

(b)
Z
f 0 (x)
dx = ln f (x) + C.
f (x)

2
These two results are readily established by means of the substitution
u = f (x).
In both cases du
dx
= f 0 (x) and hence dx
du
= 1
f 0 (x)
. This converts the integrals, respectively, into

(a)
Z
un+1
un du = +C
n+1
and (b) Z
1
du = ln u + C.
u

EXAMPLES

1. Evaluate the definite integral


Z π
3
sin3 x. cos x dx.
0

Solution
In this example we can consider sin x to be f (x) and cos x to be f 0 (x).
Thus, by quoting result (a), we obtain

sin4 x
π
"
Z
3
3
9
sin3 x. cos xdx = = ,
0 4 0
64

using sin π3 = 2
3
.
2. Integrate the function
2x + 1
x2 + x − 11
with respect to x.
Solution
Here, we can identify x2 + x − 11 with f (x) and 2x + 1 with f 0 (x).
Thus, by quoting result (b), we obtain
Z
2x + 1
dx = ln(x2 + x − 11) + C.
x2 + x − 11

3
12.4.3 EXERCISES

1. Use the substitution u = x + 3 in order to determine the indefinite integral


Z √
x 3 + x dx.

2. Use the substitution u = x2 − 1 in order to evaluate the definite integral


Z 5 √
x x2 − 1 dx.
1

3. Integrate the following functions with respect to x:


(a)

sin7 x. cos x;
(b)
cos5 x. sin x;
(c)
4x − 3
;
2x2 − 3x + 13
(d)
cot x.

12.4.4 ANSWERS TO EXERCISES

1.
2 5 3
(x + 3) 2 − 2(x + 3) 2 + C.
5
2.
5
1 2 1 3

3
(x − 1) 2 = 24 2 ' 39.192
3 1 3

4
3. (a)
sin8 x
+ C;
8
(b)
cos6 x
− + C;
6
(c)
ln(2x2 − 3x + 13) + C;
(d)

ln sin x + C.